The communist subversion of Czechoslovakia, 1938-1948 : the failure of coexistence - Korbel, Josef (Princeton, N.J. : Princeton University Press, 2015)
From the fateful days of the Munich crisis in September 1938 to the final coup in February 1948, the Communists gradually infiltrated Czechoslovakia. This is the record of that tragic conquest, written by the former head of Jan Masaryk's Cabinet in the Czechoslovak Ministry of Foreign Affairs. Mr. Korbel reveals the gradual erosion of all areas of the nation's life-political, economic, cultural, military, social-by Communist techniques. He traces the hopeless attempts at coexistence on the part of such democratic statesmen as Edvard Benes and Jan Masaryk, as they tried to negotiate with such Communists as Klement Gottwald and Stalin himself. The campaign of infiltration followed a preconceived plan, first capturing the mind through persuasion and protestations of nationalism, freedom, democracy; then moving inexorably from the local to the national level, in labor unions, political organizations, channels of communication, the police, the army, the government. This is a moving and objective record of an important event in modern history, and a revealing case study of the Communist capture of a country. Mr. Korbel has based his account on interviews with participants, on unpublished memoirs and documents, on Communist materials published after their seizure of power, and on his own firsthand knowledge and experience. Originally published in 1959. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Looking back -- The Communist party of Czechoslovakia -- From Munich to Super-Munich -- In the guise of patriots -- A fateful journey -- The struggle begins -- In the "liberated" homeland -- Infiltration in width and depth -- A mutual offensive -- The crush -- The long night.
Online resource; title from PDF title page (EBSCO, viewed November 3, 2015)
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Czechoslovakia -- History -- 1938-1945.; Czechoslovakia -- History -- 1945-1992.; Communism -- Czechoslovakia; Tchécoslovaquie -- Histoire -- 1938-1945.; Tchécoslovaquie -- Histoire -- 1945-1992.; HISTORY -- Europe -- Germany; POLITICAL SCIENCE -- Political Ideologies -- Communism, Post-Communism & Socialism; Communism; Czechoslovakia; 1938-1992; History